Pembangunan Database Destinasi Pariwisata Indonesia dan Implementasinya pada Sistem Berbasis Web - Yosafati Hulu (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Regarding to: (1) the increasing region’s need in developing tourism destinations; (2) the needs of tourists in selecting appropriate attractions according to specified criteria; (3) the need of travel businesses to offer sights of interest in accordance with the needs of potential tourists, (4) the need to deepen and continue our previous research titled "Development of Tourism Destination Media Potential and Utilizing Local Resources in the Era of Autonomy and Regional Expansion ", we need to develop a complete database of tourism destinations in Indonesia that can facilitate those needs. We build a web-based database that is capable of storing complete information about Indonesian tourism destinations in thorough, systematic, and structured way. It is also able to classify a variety of attractions based on attributes such as: location (the name of the island, province, district), type/ tourism products, how to achieve the object, cost, and a variety of informal information, such as the ins and outs of the attraction area incorporated by the local or tourist experiences. The research will focus on deepening and refinement of the model and database structure design and implementation with the collection, processing, and data entry of primary and secondary data which amounts to approximately 140 tourism destinations in Indonesia. The research is arranged in stages as follows: (1) designing models and the database structure, (2) making a web-based program, (3) installation and hosting ; (4) data collection, (5) data processing and data entry, (6) evaluation and improvement/ refinement. Once developed, the database can be used as a starting point in the development of Data Warehouse, Decision Support System, and Expert System for Indonesian tourism industry.